Editorial [Optica Applicata, Vol. 35, 2005, nr 4] - Wilk, Ireneusz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The present issue of Optica Applicata is composed of three parts. The first two parts devoted to porous and special glasses contain developed forms of the contributed papers presented at the 7th Seminar Porous Glasses – Special Glasses PGL, 2005 (Szklarska Porêba, Poland, September 10–14, 2005) being next subjected to the respective reviewing procedures accepted in our journal. The third part includes the other articles from different fields accepted for publications in the usual procedure.
Optica Applicata, Vol. 35, 2005, nr 4, s. 675-676
Keywords: optyka; editorial